2018
DOI: 10.1177/2055116918764589
|View full text |Cite
|
Sign up to set email alerts
|

Severe oesophageal constriction due to an aberrant right subclavian artery with Kommerell’s diverticulum in a cat

Abstract: Case summaryA 6-month-old female cat with a history of chronic regurgitation presented with weight loss. CT angiography (CTA) showed severe constriction of the oesophagus due to an aberrant right subclavian artery and Kommerell’s diverticulum. The cat was surgically treated and remained clinically normal. More than 1 year after surgery, the general condition of the cat was stable and body weight had increased.Relevance and novel informationThis case report describes the clinical findings and surgical managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…In this study, the HNCM and HOCM had decreased LV-SL in whole layers and LV-SC in the epicardium, which is consistent with the results of previous studies (20). Previous 2D-STE studies in cats with HCM have reported lower longitudinal strain in asymptomatic HCM cats than in healthy cats (13,19).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, the HNCM and HOCM had decreased LV-SL in whole layers and LV-SC in the epicardium, which is consistent with the results of previous studies (20). Previous 2D-STE studies in cats with HCM have reported lower longitudinal strain in asymptomatic HCM cats than in healthy cats (13,19).…”
Section: Discussionsupporting
confidence: 92%
“…However, LV-SC Endo/Epi was decreased in the HOCM and HNCM compared to the healthy cats, although the difference was not significant. LV-SC Endo/Epi in asymptomatic cats-affected HCM was increased compared to healthy cats in a previous study, although there was no significant difference in LV-SL Endo/Epi (20). Increased LV-SC Endo/Epi is considered to be circumferential endocardial compensation for depressed epicardial contraction (20,23,24).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Physical obstruction of the esophagus by aberrant vasculature is occasionally encountered. [7][8][9][10] Lesions of the central nervous system have not been reported to cause megaesophagus in cats. However, peripheral neuropathies are common causes of megaesophagus, with feline dysautonomia being reported frequently.…”
Section: Introductionmentioning
confidence: 99%